The House on Diamond Hill : A Cherokee Plantation Story - Miles, Tiya, 1970- (Book collections on Project MUSE., 2010)
At the turn of the nineteenth century, James Vann, a Cherokee chief and entrepreneur, established Diamond Hill, the most famous plantation in the southeastern Cherokee Nation. In this first full-length study to reconstruct the history of the plantation, Tiya Miles tells the story of Diamond Hill's founding, its flourishing, its takeover by white land-lottery winners on the eve of the Cherokee Removal, its decay, and its renovation in the 1950s. Vividly written and extensively researched, this history illuminates gender, class, and cross-racial relationships on the southern frontier.